Stereoselective Regulations of P-Glycoprotein by Ginsenoside Rh2 Epimers and the Potential Mechanisms From the View of Pharmacokinetics - Zhang, Jingwei; Zhou, Fang; Niu, Fang; Lu, Meng; Wu, Xiaolan; Sun, Jianguo; Wang, Guangji (PLOS ONE, 2012)
Chirality is an interesting topic and it is meaningful to explore the interactions between chiral small molecules and stereoselective biomacromolecules, with pre-clinical and clinical significances. We have previously demonstrated that 20(S)-ginsenoside Rh2 is an effective P-glycoprotein (P-gp) inhibitor in vitro and in vivo. Considering the stereochemistry of ginsenoside Rh2, in our present study, the regulatory effects of 20(R)-Rh2 on P-gp were assayed in vivo, and the differential regulations of P-gp by ginsenoside Rh2 epimers in vivo were compared and studied. Results showed that 20(S)-Rh2 enhanced the oral absorption of digoxin in rats in a dose-dependent manner; 20(R)-Rh2 at low dosage increased the oral absorption of digoxin, but this effect diminished with elevated dosage of 20(R)-Rh2. Further studies indicated stereoselective pharmacokinetic profiles and intestinal biotransformations of Rh2 epimers. In vitro studies showed that Rh2 epimers and their corresponding deglycosylation metabolites protopanaxadiol (Ppd) epimers all exhibited stereoselective regulations of P-gp. In conclusion, in view of the in vitro and in vivo dispositions of Rh2 and the regulations of P-gp by Rh2 and Ppd, it is suggested that the P-gp regulatory effect of Rh2 in vivo actually is a double actions of both Rh2 and Ppd, and the net effect is determined by the relative balance between Rh2 and Ppd with the same configuration. Our study provides new evidence of the chiral characteristics of P-gp, and is helpful to elucidate the stereoselective P-gp regulation mechanisms of ginsenoside Rh2 epimers in vivo from a pharmacokinetic view.